Message - Nassar, Dr. Ibrahim F. (Universal Journal of Pharmaceutical Research, 2020)
Are there laboratory experiments stating that the nigella eliminates the crown virus "Covid"? From what was inferred by some to conclude that the black seed has the ability to eliminate the crown virus, the results of laboratory research of a team of researchers at a medical institute in Turkey found that the experiments were carried out on cancerous cells and not on humans, and that the virus that was used is the type of coronavirus (Corona) - M.H.A. 59 - which is hostile to mice and not to humans, and does not affect the lung, but mostly the liver, kidney, and sometimes the brain. Here we have the virus - MHA 59 - differs completely and in detail from the crown virus-2019 (covid), which - that is, covid - antagonizes humans and not mice, and has the property of infecting the human lung in the first degree, not the liver or the brain, as the two strains differ In terms of the kind that incubates them (mouse versus human), and in terms of the type of disease that causes them, and then most likely to have two different treatments. Not to mention that one of the constants of experimental sciences and the development of drugs is that any drug can in no way be considered beneficial against a specific disease except by conducting direct experiments on a large number of patients (clinical trials), in a controlled study and the exact conditions that are not available here to go into, and must The study includes a controlled or controlled trial in which patients receive a "placebo", and compares the improvement of the condition of patients who took the placebo with the case of those who took the real drug. Drug development, as is known to experts, goes through several stages, the first and easiest, experiments on cells, then experiments are conducted on animals, and then the drug passes the first stage of clinical tests, in which only the safety of the beginning is tested, so that different amounts of the drug are tested in healthy people , Then the drug itself may be harmful and has serious side effects, and if the drug succeeds at this stage, then it passes through other stages to reach the stage of its use directly on patients. In many cases, the drug succeeds in the experiments on cells and animals, but it fails in human experiments, as a single cell is not like a complex body that contains different organs, hormones, etc. The human body differs from the bodies of animals, and therefore not every drug that shows effectiveness on individual cells or animals, will have the same effect in humans. There is no empirical research that states that in the black seed is a treatment against the crown epidemic of Covid, it is ignorance that a person will leap from experiments on cells or even animals, to infer the effect of a drug on humans, this is almost a criminal act, especially if the drug causes itself harmful to the human being, or if the patient can recover from illness with the use of a real medicine, then it was dispensed with a hypothetical drug, which was adorned for him by ignorance of the experimental sciences. UJPR is an International journal that gathers editors and researchers from all over the world. Each published research paper in the journal has been review through several stages to maintain the quality of paper of journal and strictly follow public ethics. I congratulate all the researchers for their contribution in this issue and welcome the eminent and younger for the next issue. A heritage to be carried, a dream to be nurtured, a goal to be succeeded, an era to be generated UJPR is a small step toward that mountain to be climbed.